“Plus que jamais nécessaires”: Cultural Relations, Nationalism and the State in the Canada-Québec-France Triangle, 1945–1960 - Meren, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractCharles de Gaulle’s cry of “Vive le Québec libre!” during his 1967 visit to Montreal was the product of the convergence of Canadian, Quebecois and Gaullist nationalist reactions to preponderant US influence and globalization’s rise after 1945. The dynamic was especially pronounced in the cultural sphere. Consistent with the trend towards increased transnational exchanges, cultural relations grew in the Canada-Quebec-France triangle in the fifteen years after the Second World War. Quebec neo-nationalism’s rise was accompanied by a greater appreciation of France as an ally as Quebec strove to preserve its francophone identity. Such preoccupations corresponded to French apprehensions about the ramifications on France at home and abroad of American cultural ‘imperialism.’ In addition to nationalist concerns in France and Quebec, English Canadian nationalists were preoccupied with American influences on the Canadian identity. If these three interacting nationalist reactions shared a preoccupation about American cultural power and Americanization that encouraged a growing state involvement in culture and promoted greater exchanges, the differences between them also helped set the stage for the tempestuous triangular relationship of the 1960s.